백내장 수술의 질 관리정책이 비급여렌즈 사용에 미친 영향 분석 - 박재일; Chae-il Park; 원영주; Young-joo Won; 박명배; Myung-bae Park; 장한솔; Han-sol Jang; 이광수; Kwang-soo Lee (Health policy and management, 2025)
연구배경: 본 연구는 2023년 백내장 수술의 적정성 및 질 관리를 목표로 시행된 [질병군] 고시(No. 2022-293) 개정안이 백내장 수술에서 비급여 렌즈 사용에 미친 영향을 실증적으로 분석하고자 한다. 방법: 2020년부터 2024년 3월까지 건강보험심사평가원에 청구된 백내장 수술 자료(N=2,679,307)를 활용하여, 고시 시행 여부(독립변수)에 따른 비급여 렌즈 사용(종속변수)의 변화를 분석하였다. 비급여 렌즈 사용 여부는 세부 코드 “MT060”을 통해 확인하였으며, 성별, 연령, 지역, 종별 유형을 통제하여 로지스틱 회귀분석을 수행하였다. 결과: 고시 시행 이후 비급여 렌즈 사용량은 유의미하게 감소한 것으로 나타났으며(odds ratio, 0.78; 95% confidence interval, 0.78-0.79; p<0.001), 여성 및 젊은 연령층에서 사용 비율이 더 높게 나타났다. 또한 광역시 거주자가 비광역시 거주자보다 비급여 렌즈 사용비율이 높았으며, 의료기관 종별로는 의원에서 병원이나 종합병원보다 사용률이 더 높은 것으로 나타났다. 결론: 본 연구는 개정된 고시가 백내장 수술에서 비급여 렌즈 사용 감소와 의료서비스 적정성 향상에 기여했음을 보여주었다. 이는 과잉진료 억제를 포함한 보건의료 자원관리에 있어 정책 개입의 효과를 시사한다. 따라서 향후 연구에서 고시 시행 전후의 장기적 추세 변화를 보다 정밀하게 파악하여 정책의 순효과를 면밀히 검토할 필요가 있다. Background: This study evaluates the impact of the partially revised [Disease Group] Notice (No. 2022-293), implemented in 2023, on reducing the use of non-covered lenses during cataract surgeries in South Korea. It aims to empirically assess the effects of the amendments on non-covered lens utilization. Methods: Using claim data for cataract surgeries (N=2,679,307) submitted to the Health Insurance Review and Assessment Service from 2020 to March 2024, this study examined changes in the use of non-covered lenses (dependent variable) associated with the implementation of the revised [Disease Group] Notice (No. 2022-293) (independent variable). Non-covered lens use was identified using the detail code “MT060”. Logistic regression analysis was conducted, adjusting for gender, age, region, and healthcare institution type. Results: Non-covered lens usage significantly declined following the implementation of the revised notice (odds ratio, 0.78; 95% confidence interval, 0.78-0.79; p<0.001). Utilization rates were higher among women and younger patients, while residents of metropolitan areas showed greater usage compared to those in non-metropolitan regions. Clinics reported higher usage rates than hospitals and general hospitals. Conclusion: This study demonstrated that the revised notice contributed to reducing the use of non-covered lenses in cataract surgeries and improving the appropriateness of healthcare services. These findings suggest the effectiveness of policy interventions in managing healthcare resources, including the mitigation of unnecessary medical procedures. Therefore, future studies should more precisely assess the long-term trends before and after the policy implementation to thoroughly evaluate its overall effects.